Youth farmers’ willingness to Pay for agricultural extension service in Oyo State (2018)
The sustainability of agriculture calls for effective agricultural extension service delivery. However, the public agricultural extension system is grossly ineffective owing to diverse challenges including lack of funding, therefore in searching for new funding and delivery alternatives in addition to government’s input, issues such as willingness of famers to pay are extremely important. This study assessed the willingness of young farmers to pay for agricultural extension services in Ibarapa Areas of Oyo State. The population of the study consisted of all young farmers in Ibarapa Zone of Oyo State i.e. Ibarapa East, Ibarapa Central and Ibarapa North Local Government Area. Multi-stage sampling procedure was used to select one hundred and twenty young farmers. Data were collected with the aid of interview schedule. Frequency and percentages were used to describe the dependent and independent variables of the study while Pearson Product Moment Correlation (PPMC) and Chi-square were employed for hypotheses testing. The result of the findings revealed that the mean age was 32±2.8 years, majority (80.8%) were male, married (80.8%) with household size of 1-4. More than half of the respondents (54.2%) had tertiary education. Friends and family (1.85) ranked 1st as respondents’ source of information on agricultural practices. Information on credit sources (0.87) ranked 1st as the preferred agricultural service the respondents were willing to pay for. Also, less than half (47.5%) of the respondents had favourable attitude towards public extension services. However, willingness of young farmers to pay for extension services was high (51.7%). The results also revealed that there was a significant relationship between household size (χ2=9.498, p=0.023), level of education (χ2=17.454, p=0.002) and willingness to pay for extension services. Nevertheless, there was no significant relationship between respondents’ attitude towards public extension service (r=--0.150, p=0.102) and willingness to pay for extension services. The study concluded that young farmers in the study area were willing to pay for extension service.